Learning, leverage and stability. (2017) - Howitt, Peter
I construct and analyse a simple general equilibrium model with an active credit market in which borrowers and lenders form expectations adaptively. Except for expectation formation the model is a small open economy variant of the standard Lucas (1978) tree model. To abstract from institutional detail there is just a representative investor/borrower and a representative lender (rest of the world), both of whom are learning from experience. The point is to show that even in this fairly standard model financial crises can occur, and to examine the conditions, with respect to policy, institutions and other aspects of the environment, that affect the likelihood of crises in the model.